Preliminary Report on Scientific Work on "Fletcher's Ice Island", T3 - Crary, A.P.; Cotell, R.D.; Sexton, T.F. (ARCTIC, 1952)
"T3 is an ice island in the Arctic Ocean on which a permanent campsite was erected in 1952 for scientific operations. The investigations, other than meteorological, in progress from April 1-Oct. 1, included studies of the physical structure of the island, the movement of the island and the ice pack, seismic profiling and other miscellaneous data. T3 is 31 mi in circumference and has a minimum width of 5 mi. A 52-ft hole was dug in which 58 dirt layers were found, the contents of which were weighed and microscopically examined. Lakes appeared in the hollows during the thaw period (late June to mid-Aug.). A map presents the track of T3, indicating the changes of island azimuth to true and magnetic north and the geographical longitudes. A tentative ice thickness of about 160 ft was obtained through seismic soundings of the ice and the ocean bottom. Ocean depths ranging from 5000-12,000 ft were obtained."--SIPRE. Samples of surface dirt, flora and fauna were collected, including large boulders of granitic rock, plant fragments (stems, leaves, blossoms), mollusc shells, fishbones, caribou antlers, etc. A few birds and bear and arctic fox tracks were seen. Continuing research on T-3 is indicated.